Monitoring Economic Vulnerability and Performance: Applications to the Philippines - Mario B. Lamberte; Josef T. Yap (Philippine Institute for Development Studies (PIDS), 2001)
The recent spate of banking and currency crises has underscored the need to develop early warning systems. These are based on economic indicators of vulnerability, which can be identified from models and theories of crises. First generation models focus on the inconsistency of macroeconomic policies and the exchange rate peg. Examples of economic indicators derived from this framework are the fiscal deficit, growth of money supply, current account balance and the level of foreign exchange reserves. Second generation models revolve around the possibility of self-fulfilling crises and multiple equilibria. Meanwhile, the 1997 East Asian financial crisis spawned research on third-generation models, which integrated balance sheets of banks and corporations in the framework of second-generation models. The next step is then to combine all the variables in a meaningful way that will allow the prediction of economic crises. There are two popular approaches: the probability model using limited dependent variables estimation and the signals approach of Kaminsky and Reinhart. Both these methodologies have their own advantages and disadvantages but their usefulness would be constrained by the availability and timeliness of high-frequency data.
Keywords: 330; early warning system; currency and banking crisis; leading indicators; economic vulnerability; Währungskrise; Bankenkrise; Wirtschaftskrise; Wirtschaftspolitisches Ziel; Philippinen